2019
DOI: 10.1016/j.cbi.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The oral administration of silver nanoparticles activates the kynurenine pathway in rat brain independently of oxidative stress

Abstract: In this work, we determined whether oxidative stress contributed to the activation of the kynurenine pathway by AgNPs. Male Wistar rats weighing between 130 and 146 g were randomly assigned into six groups. Animals in the negative control group were orally administered distilled water while, the other treatment groups were respectively given AgNPs (25 and 50 mg/kg bw) alone or in combination with Trolox (100 mg/kg bw). Results showed that treatments with AgNPs significantly raised protein carbonyl level in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…More so, the kynurenine pathway can be activated in presence of oxidative stress and inflammation [11]. In contrast, recent studies revealed that kynurenine pathway activation in the rat brain by AgNPs was independent of oxidative stress [11]. This finding may indicate that kynurenine pathway activation in the rat brain may be through other means including the inflammatory signalling processes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More so, the kynurenine pathway can be activated in presence of oxidative stress and inflammation [11]. In contrast, recent studies revealed that kynurenine pathway activation in the rat brain by AgNPs was independent of oxidative stress [11]. This finding may indicate that kynurenine pathway activation in the rat brain may be through other means including the inflammatory signalling processes.…”
Section: Introductionmentioning
confidence: 95%
“…Together, these facts link free radical production and cytokine modulation to kynurenine pathway activation [10]. More so, the kynurenine pathway can be activated in presence of oxidative stress and inflammation [11]. In contrast, recent studies revealed that kynurenine pathway activation in the rat brain by AgNPs was independent of oxidative stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…Where appropriate, biochemical assays were performed by a spectrophotometric method using a UV/Vis spectrophotometer (Jenway, Staffordshire, United Kingdom). The test for kynurenine followed an established protocol [ 19 ]. Methods to determine the nitric oxide level (nitrite/nitrate concentration) and the total antioxidant capacity (TAC) are described elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Also, the imbalance in reactive oxygen species (ROS) produced results in oxidative stress and dysfunction in axoplasmic transport and, eventually, neuronal cell death [ 13 ]. Furthermore, compromised redox homeostasis resulting from hypoxia and kynurenine pathway activation [ 14 , 15 ] plays a role in neurodegeneration [ 16 , 17 ]. Discussed below are the major factors or conditions contributing to neurodegeneration.…”
Section: Factors Influencing Neurodegenerationmentioning
confidence: 99%